2013
DOI: 10.17795/jhealthscope-8797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Vibration Training on Delayed Onset Muscle Soreness in Young Non-Athlete Women

Abstract: Background: Delayed onset muscle soreness (DOMS) is the sensation of stiffness and pain in the muscles that occurs 24-48 hours after unaccustomed or strenuous exercise. Objectives: The aim of this study was to examine and compare the effect of vibration training (VT) on Delayed onset muscle soreness. Materials and Methods: Twenty healthy non-athletic volunteers (Female, age 20-30 years, body mass 23.27 ± 0.82 kg) were randomly assigned to VT (n = 10) and non-VT (n = 10) groups. A vibrator was used to apply 50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The results of heterogeneity examination suggest that Aminian-Far study (1) in VAS and Kamandani study (29) in PPT and CK contributed to the high heterogeneity for each subgroup. With respect to the heterogeneity in PPT and CK, it was found that the amplitude of vibration in the study of Kamandani et al (29) was 12 mm, which was significantly higher than other included studies in which vibration amplitudes were around 2-5 mm. Thus, further research is warranted to explore the effect of different vibration amplitudes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results of heterogeneity examination suggest that Aminian-Far study (1) in VAS and Kamandani study (29) in PPT and CK contributed to the high heterogeneity for each subgroup. With respect to the heterogeneity in PPT and CK, it was found that the amplitude of vibration in the study of Kamandani et al (29) was 12 mm, which was significantly higher than other included studies in which vibration amplitudes were around 2-5 mm. Thus, further research is warranted to explore the effect of different vibration amplitudes.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, it was also shown that pre-exercise VT was more effective than postexercise VT (31). According to Kamandani et al (29), performing WBV (30–50 Hz, 12 mm, 6 minutes divided in 5 bouts lasting 30–60 seconds each with 30 seconds rest in between bouts) before downhill running on the −5° treadmill at 5–7.5 km·h −1 could decrease subsequent muscle damage and DOMS shown by CK and PPT measured on quadriceps and calf muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that vibration was highly effective for muscle damage recovery, acceleration of muscle neural activation recovery 7 , 13 , 20 ) ; however, some studies have reported that vibration has a negative effect on muscle fatigue or muscle weakness 6 , 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The overall picture is encouraging, with meta-analysis finding vibration effective for prevention or treatment of DOMS [ 29 , 30 ]. Therapies studied include those provided before [ 31 – 36 ] and after [ 9 , 20 , 35 , 37 – 49 ] exercise; in athletes [ 36 , 49 ], untrained [ 9 , 31 35 , 37 , 38 , 40 , 42 , 45 , 47 , 48 ] and recreationally active [ 20 , 39 , 41 , 43 , 44 , 46 ] participants; and using local vibration [ 20 , 31 , 32 , 34 , 35 , 37 , 38 , 40 , 45 , 48 , 49 ] and WBV [ 9 , 33 , 36 , 39 , 41 44 , 46 , 47 ]. However, the specific case of WBV used post-exercise in elite athletes has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%